The Effect on Audit Quality of Auditing along the Supply Chain - Zang, Yoonseok (Institutional Knowledge at Singapore Management University, 2013)
This paper investigates whether auditors, at the office level, that audit both a supplier and the supplier’s major customer firms (i.e., supply chain specialist auditors) exhibit higher audit quality to their clients (i.e., the supplier firms). We find that supply chain specialist auditors are more likely to issue a going concern opinion and are better able to constrain opportunistic earnings management as captured by abnormal accruals of their client firms. Moreover, we find evidence indicating that the positive association between audit quality and supply chain specialist audits is more pronounced for audits provided by non–Big 4, non-industry specialist, and non-local auditors, than by Big 4, industry specialist, and local auditors, respectively. These findings suggest that information advantages arising from simultaneous auditing of both suppliers and customers help supply chain specialist auditors to improve audit quality and that these advantages are more beneficial for traditionally claimed lower-quality auditors.